2010
DOI: 10.1091/mbc.e09-06-0530
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-interacting Protein Shuttles between Cell Death and Survival Signaling Pathways

Abstract: RIP shuttles between CD95/Fas death and FAK survival signaling to mediate anoikis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 37 publications
0
45
0
Order By: Relevance
“…For instance, although RIP1 is not required for apoptosis induced by agonistic anti-Fas antibody or crosslinked FasL, it promotes caspase 8 activation within the receptor-associated death inducing signal complex (DISC) and apoptosis in response to membrane-bound FasL [21]. In addition, RIP1 is required for detachment-induced, Fas-mediated anoikis [22]. Inhibitor of apoptosis (IAP) antagonists are small molecule mimics that sensitize cells to apoptosis by inducing autoubiquitylation and proteasomal degradation of cIAP1 and cIAP2, and the autocrine production of TNF [23, 24].…”
Section: Rip1: a Pleiotropic Kinase Controlling Cell Survival And Celmentioning
confidence: 99%
“…For instance, although RIP1 is not required for apoptosis induced by agonistic anti-Fas antibody or crosslinked FasL, it promotes caspase 8 activation within the receptor-associated death inducing signal complex (DISC) and apoptosis in response to membrane-bound FasL [21]. In addition, RIP1 is required for detachment-induced, Fas-mediated anoikis [22]. Inhibitor of apoptosis (IAP) antagonists are small molecule mimics that sensitize cells to apoptosis by inducing autoubiquitylation and proteasomal degradation of cIAP1 and cIAP2, and the autocrine production of TNF [23, 24].…”
Section: Rip1: a Pleiotropic Kinase Controlling Cell Survival And Celmentioning
confidence: 99%
“…We recently showed that receptor interacting protein (RIP), shuttles between CD95/Fas death and FAK survival signaling pathways to mediate anoikis in OSCC cells 10 . Hence, under anoikis conditions, FAK and RIP dissociate, leading to the association of RIP with Fas and the formation of the death inducing signaling complex, thus enhancing apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that anoikis activates a CD95/Fas-mediated signaling pathway regulated by receptor interacting protein (RIP), a kinase that shuttles between CD95/Fas-mediated cell death and integrin/FAK-mediated survival pathways in oral squamous cell carcinoma (OSCC) cells [69]. Interestingly, we found that, as OSCC cells become resistant to anoikis, their SIRT3 expression increases and their RIP expression decreases.…”
Section: Sirt3 and Cell Survivalmentioning
confidence: 99%
“…Anoikis, apoptotic cell death triggered by loss of extracellular matrix (ECM) contacts, is dysregulated in many chronic debilitating and fatal diseases, including cancer, and resistance to anoikis contributes to the development and progression of cancer [68,69,70]. We recently reported that anoikis activates a CD95/Fas-mediated signaling pathway regulated by receptor interacting protein (RIP), a kinase that shuttles between CD95/Fas-mediated cell death and integrin/FAK-mediated survival pathways in oral squamous cell carcinoma (OSCC) cells [69].…”
Section: Sirt3 and Cell Survivalmentioning
confidence: 99%